HUBUNGAN ANTARA LAMA HEMODIALISIS DAN FAKTOR KOMORBIDITAS DENGAN KEMATIAN PASIEN GAGAL GINJAL KRONIK DI RSUD DR. PRINGADI MEDAN - MARLINA RAJAGUKGUK (LP2MTBM MAKARIOZ, 2019)
Kidney disease is a global health problem seen from the increase of incidence, prevalence, and morbidity rate. Hemodialyisis is the most widely used therapies by patients with chronic renal failure to improve survival. Patients with chronic renal failure undergoing hemodialysis at Dr.Pringadi Medan hospital continues increasing each year. This study aimed to determine the relationship among length of hemodialysis,cormobidity factors and mortality of chronic renal failure ptients in RSUD Dr.Pringadi Medan. This type of study was an observational case-control design. Sampling techniques in cases and controls used consecutive sampling. Statistical tests used to analyze the data of this study is the chi square test. The research result showed that there was a significant relationship among diabetes mellitus type II (p = 0.046; OR = 2.852; CI = 0.995-8.173), diabetic nepropathy (p = 0.002; OR = 6.714; CI = 1.803-24.998), heart failure (p = 0.004; OR = 4.636; CI = 1.553-13.84), length of hemodialysis (p = 0.028; OR = 2.455; CI = 1.097-5.494) and mortality of patients with chronic renal failure, then there was no siginificant relationship among hypertension (p = 0.839; OR = 1.086; CI = 0.489-2.411), anemia (p = 0.523; OR = 0.762; CI = 0.33-1.758) and death of patients with chronic renal failure.